2005
DOI: 10.1074/jbc.m414065200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of Cardiac KATP Channel Activation by Epoxyeicosatrienoic Acids

Abstract: We have previously reported that epoxyeicosatrienoic acids (EETs), the cytochrome P450 epoxygenase metabolites of arachidonic acid, are potent stereospecific activators of the cardiac K ATP channel. The epoxide group in EET is critical for reducing channel sensitivity to ATP, thereby activating the channel. This study is to identify the molecular sites on the K ATP channels for EET-mediated activation. We investigated the effects of EETs on Kir6.2⌬C26 with or without the coexpression of SUR2A and on Kir6. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Additional studies indicated that the EETs can directly interact with cellular proteins. Patch-clamp experiments have shown that EETs can directly interact with myocardial Na ϩ and ATP-sensitive K ϩ (K ATP ) channels (94,100), and the latter finding is consistent with the fact that an EET binding site has been detected in the K ATP ion channel (99). EETs also bind to intracellular proteins that contain fatty acid binding sites, including FABPs and PPAR␥ (97,161).…”
Section: Intracellular Mechanismsupporting
confidence: 63%
See 1 more Smart Citation
“…Additional studies indicated that the EETs can directly interact with cellular proteins. Patch-clamp experiments have shown that EETs can directly interact with myocardial Na ϩ and ATP-sensitive K ϩ (K ATP ) channels (94,100), and the latter finding is consistent with the fact that an EET binding site has been detected in the K ATP ion channel (99). EETs also bind to intracellular proteins that contain fatty acid binding sites, including FABPs and PPAR␥ (97,161).…”
Section: Intracellular Mechanismsupporting
confidence: 63%
“…EETs bind to the myocardial K ATP channel and thereby reduce its sensitivity to ATP by an allosteric alteration of the ATP binding site (99,100). Activation of the mitochondrial K ATP channels protects the myocardium against ischemia-reperfusion injury (140), suggesting that myocardial preconditioning may occur through a direct interaction between EETs and the channel.…”
Section: Ion Channel Activation By Eetsmentioning
confidence: 99%
“…22 hSlo cDNA and 2 recombinant adenoviruses, AdCAT carrying CAT and AdLacZ carrying ␤-galactosidase, were used for gene transfer. 23…”
Section: Cell Culture and Hslo Cat Transfectionmentioning
confidence: 99%
“…Interaction between EET and cardiac K ATP channels is stereospecific with 11(S),12(R)-EET being the active enantiomer while 11(R),12(S)-EET is totally inactive (23). Recently, we have identified R192/R195 on Kir6.2, which encodes cardiac K ATP channels, as the critical EET sensitivity site (19). In contrast, we found that activation of vascular K ATP channels by EET is mediated by PKA-dependent mechanisms (37).…”
Section: Discussionmentioning
confidence: 96%